OS IMPACTOS DA PROVA PARANÁ EM ESCOLAS DAS REDES MUNICIPAL E ESTADUAL DE EDUCAÇÃO BÁSICA - Savaris, Sônia Bratifich (2022)
The dissertation “The impacts of the Paraná Test in schools of the municipal and state networks of Basic Education”, developed at the State University of West Paraná - UNIOESTE, Cascavel/PR campus, in the Education, Social Policies and State research line, has the objective of analyzing the impacts of Prova Paraná on schools in the municipal and state networks of Basic Education in the municipality of Cantagalo, PR, in an attempt to understand its role in building the quality of Education in Paraná. The Paraná Test is a large-scale diagnostic assessment, created by the State Department of Education (SEED) in 2019, to diagnose the learning of students in state and municipal public networks. This study was supported by documental, bibliographic and field research. To examine the perception of teachers and the management team about the Test, a semi-structured online questionnaire was used, approved by the Research Ethics Committee, sent to professionals from six schools in the municipal network and to the four schools in the network. state in the municipality of Cantagalo. The analysis of the collected data took place from the perspective of Bardin's Content Analysis (2016), in its pre-analysis, material exploration and results treatment stages. The approach is qualitative, exploratory and interpretive in nature. The theoretical corpus of the study aimed to understand the social context in which the Paraná Test is inserted, discuss the concept of quality in education and understand the concept of diagnostic assessment and large-scale assessment. As a result, the study points to the intensification of neoliberal quality in Education in Paraná, an adaptation of the concept of diagnostic evaluation to meet managerial objectives both at the state and municipal levels. The documental analysis evidences the managerial emphasis of the Test, the data demonstrate that the Paraná Test impacts the daily work of teachers, directors and pedagogues with a significant increase in work, from the organization to apply and correct, to the requirements of work with descriptors, simulated, finally, to prepare students for the Test.